Synthesis of biodiesel from soybean oil based on - Thanh, Nguyễn Văn; Bằng, Nguyễn Hữu; Ngọ, Đinh Thị; Chiến, Lê Đình (Vietnam Journal of Chemistry, 2012)
Biodiesel, consisting of methyl esters of long chain fatty acids produced by transesterification of vegetable oils or animal fats with methanol, is a promising alternative diesel fuel regarding the environmental concerns and the limited recourses of fossil fuels. In this article, an environmentally starting process for the transesterification of soybean oil to biodiesel using Na2CO3 loaded on γ-Al2O3 as a solid-base catalyst was developed. The catalyst loaded Na2CO3 of 40 wt% on γ-Al2O3, after being calcined at 300oC for 4 hours, was found to be the optimum catalyst, which can give the best catalytic activity for this reaction. The effects of various reaction variables such as the catalyst loading, oil to methanol ratio, reaction time and temperature on the conversion of soybean oil were investigated. The catalysts were characterized by XRD, TPD-NH3 and SEM methods. The results indicated that the catalysts consist two phases the activity phase and Na2CO3 distributed in the pores of γ-Al2O3.